Macrophage‐Derived microRNA‐155 Increases in Obesity and Influences Adipocyte Metabolism by Targeting Peroxisome Proliferator‐Activated Receptor Gamma. Issue 11 (18th September 2019) - Tryggestad, Jeanie B.; Teague, April M.; Sparling, David P.; Jiang, Shaoning; Chernausek, Steven D.
Abstract : Objective: This study aimed to investigate cellular sources of microRNAs (miRNA) within adipose tissue and the impact of obesity on miRNA expression, as well as to examine targets of miRNAs. Methods: miRNA expression by quantitative polymerase chain reaction was examined in adipocytes, adipose tissue macrophages (ATM), and peripheral blood mononuclear cells from and individuals with normal weight and with obesity. Differentiated 3T3‐L1 adipocytes were cocultured with macrophages, and 3T3‐L1 and differentiated human mesenchymal stem cells were transfected with miR‐155, with peroxisome proliferator‐activated receptor gamma (PPAR‐γ) and solute carrier family 2 member 4 (GLUT4) abundance measured via Western blot analysis. Results: Abundance of miR‐155 and miR‐210 was increased in ATM of participants with obesity by 6.7‐fold and 2.9‐fold ( P = 0.002 and P = 0.013, respectively). miR‐130b expression was increased 1.8‐fold in ATM and 4.3‐fold in adipocytes from participants with obesity ( P = 0.007 and P = 0.02, respectively). PPARG mRNA expression decreased 32% ( P = 0.044) in adipocytes from individuals with obesity. In 3T3‐L1 cells exposed to macrophages, PPARG expression decreased 99.4% ( P = 0.02). PPAR‐γ protein content declined 75% ( P = 0.001) in 3T3‐L1 cells transfected with miR‐155. GLUT4 protein levels were reduced by 55% ( P = 0.021) in differentiated human mesenchymal stem cells exposed to miR‐155. Conclusions: Adipose tissue miRNAs are influenced in a cell type–specific fashion by obesity, with macrophage miR‐155 potentially impacting neighboring adipocytes.